Determining the photic chronotype in locomotor activity and levels of endogenous control in the American dog tick (Dermacentor variabilis) - Joseph Giulian; Natalia Toporikova; Jessica Petko; Nadia Ayoub; Thomas C. Jones; Darrell Moore (Ticks and Tick-Borne Diseases, 2025)
It is an open question whether the activity of host-seeking ticks is under endogenous circadian control or arises entirely as an exogenous response to external stimuli. We experimentally evaluated the chronotype of locomotor activity in individual unfed adult Dermacentor variabilis. Two major activity peaks in locomotor activity arose in response to an evenly split 24-hour photic cycle. Most individuals had either a chronotype with exclusively nocturnal activity or with both nocturnal and diurnal activity components. Our results indicate that diurnal behavior has an endogenous basis but suggest that nocturnal behavior is driven by an exogenous response to the photic cycle.